Conservation of Indonesia's Natural Resources: An Overview of the Criminal Policy Perspective (Law Research Review Quarterly, 2015)
God has provided Indonesia's abundant biological natural resources. But on its way, damage and pollution occurred here and there. Strategic steps are needed to stop the rate of movement of damage to living natural resources. Early birth of Law No. 5 of 1990 concerning Conservation of Living Natural Resources and their Ecosystems is a breath of fresh air for the protection of Indonesia's biological natural resources. But until now there is still plastered data on ecosystem damage that disturbs the living natural resources. Therefore, a review of existing policies (specifically the criminal law policy / penal policy) is hoped to be able to help overcome the damage to the living natural resources. criminal system formulated by Law No. 5 of 1990 concerning Conservation of Biological Natural Resources and their Ecosystems belong to the conventional category because they still follow the pattern used by the Criminal Code (KUHP), which only recognizes legal subjects in the form of individuals (not corporates), does not know the special minimum system , and is oriented towards differentiating offenses qualifications (crime and violations).